Experiences of group antenatal care in the context of the NHS in England: what are the mechanisms by which it functions in this context? - McCourt, Christine; Mehay, Anita; Wiseman, Octavia; Lazar, Jalana; Ajayi, Ruth; Hamborg, Thomas; Holmes, Vivian; Hunter, Rachael Maree; Mishareva, Ekaterina; Safo Sobre, Pearl; Wiggins, Meg; Harden, Angela; et al. (Frontiers in Global Women's Health, 2025)
IntroductionGroup antenatal care is a model where care is provided in groups of around 6–12 women/birthing people, integrating healthcare with information and learning in a participatory approach. There is international evidence of improved care experiences and outcomes; however, the approach (here called Pregnancy Circles) had not been trialled in the United Kingdom in the context of a universal health system with midwife-led care. We aimed to understand the experience of care and any mechanisms by which group care functions for the different people involved.MethodThis study comprised a qualitative process evaluation nested within a randomised controlled trial. The mixed qualitative methods used in this study included observations of care, interviews with participants, survey open-text responses and written feedback, and a review of relevant documents. Inductive thematic analysis was conducted using a framework of theorised mechanisms based on a realist review. The trial’s clinical and psychosocial outcomes and lessons for implementation are reported elsewhere.ResultsWe found a high level of concordance with the framework of mechanisms derived from the literature. The key mechanisms were social support and community building, a critical pedagogy (combining peer learning, an interactive and participatory approach, and health education), satisfaction and engagement with care, and the health professionals’ satisfaction and development. Building on these, the empowerment of participants and midwives formed an overarching mechanism. Relational continuity and time for care were the key underpinning components.DiscussionPregnancy Circles address key deficits in contemporary maternity care, including the lack of time and relational or informational continuity of care, the lack of informed choice, and loss of opportunities to enhance empowerment through health knowledge, social support, and confidence in caring for one's own health, in decision-making, and in seeking support. Importantly, midwives felt that facilitating group care enhanced their professional satisfaction and development and collaboration across boundaries, features associated with service safety and resilience. Fidelity in terms of the midwives' skills and confidence in using a facilitative approach was important and was underpinned by continuity. Midwives' and women's empowerment were found to be mutually supportive rather than in tension. Scaling up Pregnancy Circles as a standard care option in the National Health Service may support positive care experiences; however, further research is needed to monitor the longer-term impact and service and public health implications.